The Effect of Carbohydrate Loading On Gastric Residual Volume And Hunger Score: A Single Blind, Randomised Controlled Trial Study - Chen, Lua Bee (2020)
Background Carbohydrate loading is one of the key steps in Enhanced Recovery After Surgery (ERAS) protocol which aims to expedite post-operative recovery. Body response to surgery and prolong fasting by releasing of stress hormone and inflammatory marker leads to insulin resistance and catabolic state. Objective Effectiveness of carbohydrate loading versus plain water on gastric residual volume and patient’s well being. Methodology This is a single centre, single-blinded, parallel, placebo-controlled, stratified randomized controlled trial at Endoscopy Unit, Hospital Universiti Sains Malaysia(HUSM) from May 2019 to March 2020. Patients older than 18 years old were randomly assigned to either carbohydrate loading (237mls of resource) or control group (250mls of plain water). Randomization sequence was computer generated and allocation sequence was sealed in sequentially numbered and opaque envelopes. The drinks were served 2 hours prior to OGDS procedure. During the OGDS, all the gastric contents were aspirated into a reservoir bottle and recorded as gastric residual volume for comparison later. The patients’ well-being (hunger, thirst, anxiety, tiredness, and weakness) were assessed using visual analogue scale (VAS) before (pre) and after (post) drink consumption. Results 78 patients were randomised and analysed with equal allocation between groups. Their mean age was 49 years old with standard deviation (SD) of 14.3 years old. The means (SD) gastric residual volume in carbohydrate loading group was 58.54(52.98)mls, whereas 13.97(14.93)mls in plain water group. There was significantly more gastric residual volume in carbohydrate group (p<0.001). Carbohydrate loading group significantly showed reduction in VAS score of hunger (p=0.043) and thirst (p=0.021). There was improvement of VAS score for anxiety, tiredness, and weakness over time in carbohydrate loading group compared with plain water group, but not statistically significant. Conclusion Carbohydrate loading is associated with higher gastric residual volume compared to plain water. However, they were associated with significantly better well-being.